WAQF AND ITS CONTRIBUTION IN EDUCATION IN HISTORICAL PERSPECTIVE - Asrohah, Hanun (el-Qist : Journal of Islamic Economics and Business (JIEB), 2012)
In classical Islamic education endowments have a close relationship with waqf institutions. Waqf institutions were financial resources for the activities of Islamic education that Islamic education could evolve rapidly. The existence of the Islamic waqf institution was caused by the Islamic economic system, which assumes that the economy was closely linked to the Muslims faith. Beside that, a balance between the economy and the welfare of Muslime people so that economic activities represented of worship and waqf became a way to closer to Allah and the common good. Therefore, when the Islamic economic progress, Muslims did not hesitate to spend money for the sake of religion and the welfare of Muslims. Driven by the teachings of Islam that respects the function of education for the advancement of religion and state, they feel compelled to spend their wealth for the implementation of education, and ultimately developing advanced Islamic education. Because of loving knowledge, raises the need to develop education by establishing institutions to teach and develop the science. With spearheaded by the Islamic rulers who love science, such as Harun al-Rashid and al-Ma'mun, stand up educational institutions for scientific activities, such as translation activities established by Harun al-Rashid, who at the time of al-Ma ' But the operation is perfect that resulted in the establishment Bait al-Hikmah. In further developments, the need to establish educational institutions create ideas about the need for charitable organizations that will be a source of financial institutions. Endowments role in supporting the implementation of education. With endowments, Muslims get the ease of study. Because of endowments, Islamic education was not too demanding a lot of cost for students so that they are either poor or rich have the opportunity to learned equally. Therefore, students and teachers were encouraged to perform a scientific journey.